Effect of climate variability on gender roles among communities surrounding Lake Mburo National Park, Uganda [version 1; peer review: 2 approved, 2 approved with reservations] - Elizabeth Kaase-Bwanga; Michael Ocaido; Howard Onyuth; Lawrence Mugisha; Judith Irene Nagasha (Emerald Publishing, 2019)
Background: Climate change has been increasingly recognized as a global crisis with effects on gender roles. Recently, communities surrounding Lake Mburo national park, Uganda have been experiencing frequent severe droughts. It was against this background that this study was designed to understand effect of climate change on gender roles. Methods: This cross sectional study reviewed the effect of climate change on men and women's gender roles using a pragmatic research paradigm based on a thematic review model using participatory methods and a structured questionnaire. Results: The study found that men and women's gender roles were altered during extreme dryness. Men played their roles sequentially focusing on one single productive role, while women played their roles simultaneously, balancing the demands of each role with their limited available time. Effect of climate change variability affected productive roles more in Kiruhura district than Isingiro district. There was migration of both men and women in search for water and pasture livestock in Kiruhura district which distorted gender roles of women. Consequently, women and children had a heavier load and were the most people affected by climate change effects. Conclusion: Gender roles of communities surrounding Lake Mburo National Park, Uganda were affected and altered by the effects of climate change variability. Therefore, institutions offering climate services to local communities should consider gender in decision making, access to resources, information and knowledge.